Emergence Delirium Among Older Adults in the Post-Anesthesia Care Unit: A Rapid Review - Navarro, Simon Paul P.; Ramos, Azenith S. (MALATA SAINS INDONESIA, 2026)
Introduction: Emergence delirium (ED) has been commonly recognized as a critical event within the postoperative period. Yet, evidence on its prevalence and clinical implications among older adults remains limited in the current body of knowledge. Objective: The aim of this rapid review was to elucidate and synthesize existing literature related to the key characteristics of ED and its clinical implications among older adult patients in post-anesthesia care units. Methods: The Oxford’s rapid review framework, Aveyard’s thematic analysis approach, and PRISMA checklist were followed. A systematic literature search was conducted in March 2025 across four electronic databases, including Embase, MEDLINE, CINAHL, and PubMed. Covidence software was used to assess identified primary research. The American Association of Critical-Care Nurses’ Levels of Evidence was employed to appraise and evaluate the clinical relevance of the included articles. Two authors independently screened the full text records and finalized the data extraction process. Results: Of 224 records initially screened, 69 full-text articles were assessed for eligibility, and five met the inclusion criteria. All included studies were mainly from China (n = 4) and Ethiopia (n = 1) and classified as Level C evidence. Characteristics of ED in older adults, including its risk factors, signs and symptoms, assessment tools, management strategies, and impact on patient outcomes were narratively reported in this review. Conclusion: Emergence delirium has been found to be an independent condition that potentially influences outcomes among older adult patients. The overlapping clinical picture of ED with emergence agitation and postoperative delirium warrants areas for future scientific investigation to establish accurate diagnostic tools and management for ED to improve overall patient care delivery and outcomes.